2022
DOI: 10.3390/plants11020158
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient Management Effects on Wine Grape Tissue Nutrient Content

Abstract: With limited research supporting local nutrient management decisions in North Carolina grape (Vitis vinifera) production, field studies (2015–17) were conducted to evaluate late season foliar nitrogen (N) application on leaf and petiole N concentration and yeast assimilable N (YAN) in the fruit. Foliar urea (1% v/v) was applied at different rates and application times beginning pre-and post-veraison. Compared to soil applied N, late season foliar N substantially enhanced petiole N and grape YAN. Smaller split … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…In other cases, YAN concentration did not increase when initial YAN concentration in control sample was higher than 140 mg N L −1 . 3,15,18 However, in other previous studies, YAN concentration increased when initial YAN concentration was lower 8,14,19 or higher [9][10][11][15][16][17]28 than 140 mg N L −1 .…”
Section: Amino Acids Concentration In Grapes Samplesmentioning
confidence: 65%
See 4 more Smart Citations
“…In other cases, YAN concentration did not increase when initial YAN concentration in control sample was higher than 140 mg N L −1 . 3,15,18 However, in other previous studies, YAN concentration increased when initial YAN concentration was lower 8,14,19 or higher [9][10][11][15][16][17]28 than 140 mg N L −1 .…”
Section: Amino Acids Concentration In Grapes Samplesmentioning
confidence: 65%
“…Ancín‐Azpilicueta et al 11 . found that foliar application increased pH and total acidity in Tempranillo must and Havlin et al 17 . found that malic acid concentration increased after applying urea.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations